What else is pastoral? : Renaissance literature and the environment - Hiltner, Ken (Cornell University Press, 2011)
Ken Hiltner takes a fresh look at pastoral, offering an environmentally minded reading that reconnects poems with literal landscapes, not just figurative ones.